2017
DOI: 10.1002/prot.25316
|View full text |Cite
|
Sign up to set email alerts
|

The long unstructured region of Bcl‐xl modulates its structural dynamics

Abstract: Bcl-xl protein has a long unstructured loop attached to its structured region which joins two helices. The necessity to have this unstructured segment in Bcl-xl is not yet well understood. To what extent the unstructured segment can influence the dynamics of the structured region of protein, with potential to influence the function, has been investigated in this work. Molecular dynamics simulation and principal component analysis show how the loop affects the internal motions of the protein, particularly its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
5
6
1
Order By: Relevance
“…In the porcupine plots (Figure 7), the direction of the arrow in each Cα atom characterizes the direction of the movement, while the length of the arrow represents the magnitude of the motion. The results from the eigenvector analysis of the wild-type Bcl-2 were consistent with the report published by Priya, Maity, and Ghosh (2017). Our results suggest that the concerted motion (captured by PC1, PC2, and PC3) between the two models is varied to a large extent, implicating the effect of mutation on the dynamic properties of the Bcl-2/43B binding.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 91%
“…In the porcupine plots (Figure 7), the direction of the arrow in each Cα atom characterizes the direction of the movement, while the length of the arrow represents the magnitude of the motion. The results from the eigenvector analysis of the wild-type Bcl-2 were consistent with the report published by Priya, Maity, and Ghosh (2017). Our results suggest that the concerted motion (captured by PC1, PC2, and PC3) between the two models is varied to a large extent, implicating the effect of mutation on the dynamic properties of the Bcl-2/43B binding.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 91%
“…Priya et al 53 in their computational study (100 ns ×2 in total for Bcl-xL with IDR) had reported transient interactions between the IDR and the core region of the Bcl-xL. In line with the findings of Priya et al, most of our simulations for WT and DM1 show that the loop residues E31, E32, E39 and R78 temporarily interact with core residues R165, R6, R91, and E7, respectively.…”
Section: Intrinsically Disordered Region (Idr Loop)supporting
confidence: 91%
“…Priya et al also reported that R103 (J23) and R139 (α5) of wild-type Bcl-xL behave like a gate by covering the bottom side of the binding groove compared to that of Bcl-xL without IDR. 53 We observed this type of behavior in DM1-SIM1, alas, between different residues. Most prominently, in DM1-SIM1, R102 on J23 persistently interacts with D133 (J45) (77.1 %) and E129 (α4) (45.8 %) indicating the importance of the R102 residue (Fig.…”
Section: Impact Of Deamidation On the Binding Groove (Bg)supporting
confidence: 56%
See 1 more Smart Citation
“…At the post-translational level, BCL-xL can be phosphorylated, deamidated, and ubiquitinated. Phosphorylation of BCL-xL at Ser-62 and Ser-49, have been well characterized and can alter BCL-xL intracellular localization and its loop conformation [32], which regulates the molecular association with other proteins such as BH3-only proteins and p53 [23]. Interestingly, BCL-xL proteins undergo dynamic phosphorylation/dephosphorylation on Ser-49 and Ser-62 residues during mitosis are important in the maintenance of chromosome integrity in normal cells [33].…”
Section: Bcl-xl Protein Structurementioning
confidence: 99%